Water Management in Fragile Systems : Building Resilience to Shocks and Protracted Crises in the Middle East and North Africa - Food and Agriculture Organization of the United Nations; World Bank Group (Cairo: FAO and World Bank, 2018)
This paper is part of an ongoing collaboration between the World Bank and the United Nations' Food and Agriculture Organization to raise awareness about the importance of water management in fragile systems and to propose strategic responses. It is important to better understand these dynamics to ensure that water does not add to fragility, but rather promotes stability, and contributes to resilience in the region. This paper calls for redoubling efforts towards sustainable and efficient management of water resources, reliable and affordable delivery of water services to all and protection from water-related catastrophes.